INSTITUTIONAL QUALITY, ISLAMIC FINANCE AND ECONOMIC GROWTH OF SELECTED GLOBAL SOUTH ECONOMIES - Ali, Jude Igyo (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2025)
The study examines how institutional quality moderates the relationship between Islamic finance and economic growth across emerging economies of Bangladesh, Malaysia, Indonesia, Saudi Arabia, the UAE and Pakistan from 2014 to 2023. Using panel quantile regression, it explores how Islamic finance influences growth at different levels and how institutional factors shape this relationship. Unlike earlier single-country analyses, this research adopts a comparative approach, focusing on nations that collectively account for larger percentage of global Islamic banking assets. Findings show that Islamic finance contributes positively to economic growth, with banking assets consistently beneficial across all growth quantiles. The broader Islamic finance sector exerts its strongest impact around the median growth level. Institutional quality emerges as crucial, with its positive effects more evident at higher growth quantiles. At the 75th percentile, corruption control and governance effectiveness display the greatest influence. Moreover, the interaction between Islamic finance and institutional quality strengthens at higher growth levels, suggesting that strong institutions amplify developmental benefits. Countries with robust frameworks such as Malaysia and the UAE, gain more growth dividends than weaker institutional settings like Bangladesh and Pakistan concluding that Islamic finance drive sustainable growth with strong institutions